Greater trochanteric pain syndrome: focused shockwave therapy versus an ultrasound guided injection: a randomised control trial. Issue 3 (May 2023) - Heaver, Catriona; Pinches, Megan; Kuiper, Jan Herman; Thomas, Geraint; Lewthwaite, Simon; Burston, Ben J; Banerjee, Robin D
Background: Greater trochanteric pain syndrome (GTPS) is a common problem with an incidence of 1.8–5.6 per 1000 population. Physiotherapy, anti-inflammatories, corticosteroid injections and surgery have all been described in the management of GTPS, with limited, temporal success. Extracorporeal shockwave therapy (ESWT) has been proposed as a potential non-invasive management option for this difficult presentation. Method: We ran a prospective, 2-arm, single-blinded, randomised control trial comparing focused shockwave therapy (f-ESWT) to an ultrasound guided corticosteroid injection. Primary outcome measure was the visual analogue pain score. Secondary outcome measures included the Harris Hip Score (HHS) and Trendelenburg test for function; SF-36 for quality of life (QoL); and a Likert scale question for subjective assessment of symptom improvement. Results: 104 patients (10 males and 94 females), of mean age 61.5 years were recruited. 53 were randomised to receive ESWT and 51 to receive an image-guided injection. 11 patients were lost to follow-up. There were no significant differences in baseline scores between groups. At 3 months, pain, function and QoL scores had improved in both groups but were not statistically significant. The Trendelenburg test was significantly improved in the f-ESWT group with 80% patients being negative compared to 20% at baseline ( p < 0.001). At 12 months, across all outcomes, the ESWT group had significantly improved scores compared to the injection group; VAS 37.1 versus 55.0 ( p = 0.007, 95% confidence interval [CI], 6.3–30.8), HHS 69.7 versus 57.5 ( p = 0.002, 95% CI, −20.0 to −4.6) and SF-36 52.4 versus 47.7 ( p = 0.048, 95% CI, −9.31 to −0.04). The improvement in Trendelenburg test was maintained in the ESWT group, but the injection group had reverted to baseline ( p < 0.001). Conclusions: We have shown f-ESWT is an effective treatment for patients with GTPS. We would advocate f-ESWT as an effective non-invasive treatment modality for this challenging patient population. Trial Registration No. ISRCTN8338223